Testing of Packaging and Use of Attractants to Control Fruit Flies(Bactrocera dorsalis Hendel) Guava (Psidium guajava L.) - Siregar, Ameilia Zuliyanti; Zulina, Cynthia; Bakti, Darma (Jurnal Online Pertanian Tropik, 2021)
The aims of this study to determine: The effect of kinds attractants and time of wrapping on to control of percentage of fruit fly attacks which determined the guava quality. This research was conducted in Durin Jangak Village, Pancur Batu District, Deli Serdang Regency from May to July 2019. This research was conducted using a randomized block design method with three factors: time, wrapping, attractant. The result of this research showed that the treatment by using the white plastic wrapping and attractant traps obtained the highest fruit diameter is 10.23 cm and the lowest treatment with no packaging and without attractant traps is 7.40 cm. In the treatment by using the white plastic wrapping and attractant traps obtained the highest fruit weight is 586 grams and the lowest treatment using without wrapping and attractant traps is 165 grams. At the observation of the highest trapped fruit flies in the treatment without wrapping and attractant traps that were 961 fruit flies and the lowest trapped fruit flies were white plastic wrapping treatments and attractant traps that were 790 fruit flies. In the treatment without wrapping and attractant traps,wrapping gauze and attractant traps obtained the highest percentage of fruit attack, namely 100% and treatment of white plastic wrapping and attractant traps obtained the lowest fruit attack, consist of 33%.